EFFECTS OF COMMUNICATION, MOTIVATION, WORK DISCIPLINE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT BINTANG TERANG MANDIRI - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
The aim of this research is to determine the influence of communication, motivation, work discipline and job satisfaction on employee performance. The object of this research is the consumers of PT Bintang Terang Mandiri Pekanbaru. The sample in this study was the entire population of 40 people using the census method. Data analysis uses descriptive analysis, hypothesis analysis and multiple linear regression with the help of the SPSS 21 program. The results of the research explain that communication has a positive and significant influence on employee performance, motivation has a positive and significant influence on employee performance, work discipline has a positive and significant influence on Employee performance and job satisfaction have a positive and significant influence on employee performance.